The Effect of BaCO3 Compound Changes on the Formation of Magnetic Material BaFe12O19 - Priyono, Priyono; Cahyono, Agung; Marhaendrajaya, Indras; Subagio, Agus; Gunawan, Vincensius (JURNAL SAINS DAN MATEMATIKA, 2015)
BaFe12O19 is a permanent magnetic material which has superior properties to be excellent until the late of twentieth century. Some of the obstacles in the synthesis of the material using a stoichiometric composition is a difficulty to obtain a single phase and the second phase is always found. This research attempted to make modifications on the initial non-stoichiometric composition by varying the fraction of Ba/Fe through BaCO3 and Fe2O3 compound through solid state reaction mechanism. This solid state reaction was initiated by mixing various fractions of BaCO3 and Fe2O3 powder composition and compacted to produce a homogeneous mixture using a planetary milling. After drying and molding, it was obtained a homogeneous mixture like a cylinder with a diameter of 2:54 cm and a thickness of 0.5 cm. The BaFe12O19 phase was obtained by heating the sample at a temperature of 1200 Â° C for 4 hours. To determine changes in the fraction of Ba/Fe before and after sintering, the samples were tested by X-Ray Fluorescence (XRF), while the structure and crystallinity were tested by X-ray diffraction (XRD) and Scanning Electron Microscope (SEM). The results showed that during the heating process, the reduction of barium fractions exceeded 5% from of their initial weight, while changes in the fraction of Fe was not significant. The results of structure and crystallinity measurement showed that the addition a substantial amount of barium carbonate can lead to the decrease of crystallinity from 35.271 nm to 11.265 nm.